20(S)‐Protopanaxadiol inhibits epithelial‐mesenchymal transition by promoting retinoid X receptor alpha in human colorectal carcinoma cells. Issue 24 (30th October 2020) - Lu, Zeyuan; Liu, Hongyan; Fu, Wenwen; Wang, Yuchen; Geng, Jianan; Wang, Yaozhen; Yu, Xiaofeng; Wang, Quan; Xu, Huali; Sui, Dayun
Abstract: Colorectal carcinoma (CRC) recurrence is often accompanied by metastasis. Most metastasis undergo through epithelial‐mesenchymal transition (EMT). Studies showed that retinol X receptor alpha (RXRα) and 20( S )‐Protopanaxadiol (PPD) have anti‐tumour effects. However, the anti‐metastasis effect of 20( S )‐PPD and the effect of RXRα on EMT‐induced metastasis are few studies on. Therefore, the role of RXRα and 20( S )‐PPD in CRC cell metastasis remains to be fully elucidated. RXRα with clinicopathological characteristics and EMT‐related expression in clinical samples were examined. Then, RXRα and EMT level in SW480 and SW620 cells, overexpressed and silenced RXRα in SW620 cells and SW480 cells, respectively, were evaluated. Finally, 20( S )‐PPD effect on SW620 and SW480 cells was evaluated. The results showed that a lower RXRα expression in cancer tissues, and a moderate negative correlation between RXRα and N stage, and tended to higher level of EMT. SW480 and SW620 cells had the highest and lowest RXRα expression among four CRC cell lines. SW480 had lower EMT level than SW620. Furthermore, 20( S )‐PPD increased RXRα and inhibited EMT level in SW620 cell. Finally, 20( S )‐PPD cannot restore SW480 cells EMT level to normal when RXRα silencing. These findings suggest that 20( S )‐PPD may inhibit EMT process in CRC cells by regulating RXRα expression.